Comparative Transcriptome Analysis of Hens’ Livers in Conventional Cage vs. Cage-Free Egg Production Systems - María Paula Herrera-Sánchez; Roy Rodríguez-Hernández; Iang Schroniltgen Rondón-Barragán (Veterinary Medicine International)
Different conditions of production systems including stocking density, thermal conditions, and behavior restriction can have a significant detrimental effect on the health and performance of laying hens. The conventional cage system is one of the systems that have been reported to cause stress problems in birds, due to social and behavioral stress. Emerging technologies have facilitated a deeper understanding of animal responses to various scenarios and can be an additional tool to conventional ones to assess animal welfare, where transcriptomic analysis has the potential to show the genetic changes that occur in response to stress. According to this, the aim of this work was to characterize the liver transcriptome of hens housed under two egg production systems (conventional cage and cage-free). Liver tissue from Hy-Line Brown hens housed in conventional cage (n = 3) and cage-free (n = 3) production systems at week 80 of age was processed using the Illumina platform to identify differentially expressed genes with a padj < 0.05. Regarding the differentially expressed genes, 138 genes were found, of which 81 were upregulated and 57 downregulated. Some of the genes of interest were TENM2, GRIN2C, and ACACB, which would indicate greater fat synthesis in the liver of caged hens. The enriched KEGG pathways were DNA replication and the cell cycle. In conclusion, it was identified that the cage production system may influence DNA replication and the cell cycle since the genes related to these terms were found suppressed, which would indicate cellular instability.